2019
DOI: 10.1155/2019/3027280
|View full text |Cite
|
Sign up to set email alerts
|

Disease Activity, Occupational Participation, and Quality of Life for Individuals with and without Severe Fatigue in Ankylosing Spondylitis

Abstract: Background. Fatigue is one of the most frequently reported symptoms by individuals with ankylosing spondylitis. However, it is often overlooked clinically and in research. Literature researching the impact of severe fatigue on occupational participation in ankylosing spondylitis is limited. Therefore, the aim of this research was to explore the impact of severe fatigue on occupational participation, disease activity, and quality of life in people with AS. Methods. A sequential exploratory mixed method study de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 35 publications
(61 reference statements)
4
18
2
2
Order By: Relevance
“…Besides disease activity, we also found significant associations between disease impact and fatigue. In the multi-variable analysis, physical function (measured by BASFI), and BAS-G were associated with BASDAI-fatigue, while ASQoL was associated with SF-36 VT. Our findings are consistent with other studies that reported BASFI ( 7 9 , 14 , 15 , 17 ), BAS-G ( 5 , 9 , 14 ), and ASQoL ( 6 , 9 , 14 , 15 ) as predictors of fatigue. This highlights patients' perception of fatigue as a disabling symptom and accentuates the importance of recognizing and addressing fatigue in clinical practice.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Besides disease activity, we also found significant associations between disease impact and fatigue. In the multi-variable analysis, physical function (measured by BASFI), and BAS-G were associated with BASDAI-fatigue, while ASQoL was associated with SF-36 VT. Our findings are consistent with other studies that reported BASFI ( 7 9 , 14 , 15 , 17 ), BAS-G ( 5 , 9 , 14 ), and ASQoL ( 6 , 9 , 14 , 15 ) as predictors of fatigue. This highlights patients' perception of fatigue as a disabling symptom and accentuates the importance of recognizing and addressing fatigue in clinical practice.…”
Section: Discussionsupporting
confidence: 93%
“…Spinal damage, which was measured by BASMI 10 and clustered together with age and disease duration in the PCA, was associated with SF-36 VT. However, it was not associated with fatigue measures in the multivariable analysis, which is in keeping with other studies ( 6 9 , 15 , 17 ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“… 17 The burden on individual patients with AS is not limited to health care costs associated with controlling disease activity but also encompasses costs associated with managing extra-articular manifestations, comorbidities, and disability. 18 , 19 According to data of the National Health Insurance Service-National Sample Cohort, a Korean population-based cohort with submitted medical claims between 2002 and 2013, 28% of patients with AS experienced at least one extra-articular manifestation. 9 , 20 The impact of AS on mortality has recently been highlighted in nationwide, population-based cohort studies showing that all-cause mortality is significantly increased in patients with AS compared with the general population (OR = 1.60 in a Swedish cohort), and cardiovascular mortality (OR = 1.36 in a Canadian cohort) was found to be higher in patients with AS than in controls.…”
Section: Discussionmentioning
confidence: 99%